The roles of serine protease inhibitors in dermatoses - Xiao, Zhenzhen; Kang, Yue; Zhuo, Yunqian; Li, Rui; Tan, Yingjian (Frontiers in Genetics, 2025)
The balance between proteases and their inhibitors is essential for maintaining the structural and functional homeostasis of the skin. Numerous studies have shown that serine protease inhibitors are highly expressed in the skin and play diverse roles in preserving its physiological integrity. Among them, SERPINs have been closely linked to various skin disorders—for instance, mutations in SERPINB7 are associated with palmoplantar keratoderma, while SERPINA1 has been implicated in the pathogenesis of adult-onset immunodeficiency syndrome and generalized pustular psoriasis, both of which currently have limited treatment options. This review focuses on the biological functions of SERPINs in the skin, aiming to provide insights into the mechanisms underlying SERPIN-related skin diseases and to facilitate the development of targeted therapeutic strategies.